Nasointestinal tube placement: Techniques that increase success. (February 2023) - Taylor, Stephen J; Sayer, Kaylee; White, Paul
Background: Delayed gastric emptying (DGE) is a major cause of undernutrition that can be overcome using nasointestinal (NI) feeding, but tube placement often fails. We analyse which techniques enable successful NI tube placement. Methods: Efficacy of tube technique was determined at each of six anatomical points: Nose, nasopharynx-oesophagus, stomach-upper and -lower, duodenum part-1 and intestine. Results: In 913 first NI tube placements, significant associations with tube advancement were found in the pharynx (head tilt, jaw thrust, laryngoscopy), stomach_upper (air insufflation, 10 cm or 20–30 cm flexible tube tip ± reverse Seldinger manoeuvre), stomach_lower (air insufflation, possibly flexible tip and wire stiffener) and duodenum part-1 and beyond part-2 (flexible tip and combinations of micro-advance, slack removal, wire stiffener or prokinetic drugs). Conclusion: This is the first study to show what techniques are associated with tube advancement and the alimentary tract level they are specific to.